A study on potential physical hazards at construction sites - Salim, Salim Mkubwa; Romli, Fairuz Izzuddin; Besar, Jailani; Aminian, Negin Ozve (Universiti Teknologi MARA (UiTM), Malaysia, 2017)
Statistics have shown that the number of fatality and permanent disablement cases due to accident at construction sites in Malaysia is one of the highest in comparison to other sectors. Therefore, there is an urgent need to mitigate this problem. In general, there are three basic steps that should be taken to ensure the safe and conducive working conditions: identifying the hazard, assessing the risk and controlling the risk. The implementation of effective hazards control methods may require different approaches due to changing working environment at the construction sites. This project is intended to identify and highlight the common hazards at construction sites today. The data collection was carried out through site investigation using a checklist forms and interview in construction. The study determines fourteen (14) types of work at building construction sites and their common hazards. The works include wood carpenter, bar bender, excavation work, boring rig, hacking and drill, crane work, roof work, bricks installation, scaffolding, electric welding, general activity, mechanical lifting, concreting and electrical equipment usage. The study was conducted at a building construction site and the results showed that the most common hazards for the project around the study area are associated with protective clothing, manual handling and roof work.